Effects of Propofol and Midazolam on the Inflammation of Lungs after Intravenous Endotoxin Administration in Rats - SARAÇOĞLU, AYTEN (AVES, 2015)
Objective: Pulmonary complications are important sepsis (such as ARDS, diffuse pneumonia). Acute respiratory distress syndrome (ARDS) is characterized by the extensive migration of neutrophils into alveoli of the lungs. Propofol and midazolam are the most widely used agents for sedation in intensive care units. Aimed to investigate the effects of anaesthesia with propofol and midazolam on measured hemodynamic variables and neutrophil migration induced by Escherichia Coli endotoxin (ECE) in pulmonary viscera. Materials and Methods: Forty Sprague Dawley male rats were randomly assigned to four groups: Thiopental Sodium 30 mg/kg was administered intraperitoneally to anesthetize the rats. They were ventilated via tracheotomy. Femoral artery was cannulated for the measurement of continuous blood pressure and gases. Group C was the control. After the administration of 1 mL/kg 0.9% NaCL, infusion began at 1 mL/kg/h rate. In Group E 15 mg/kg lipopolysaccharide derived from ECE was administered iv. In Group PE, after a bolus dose of 10 mg/kg propofol and 15 mg/kg ECE, 10 mg/kg/h infusion was applied. In Group ME, after 0.1 mg/kg midazolam bolus dose and 15 mg/kg ECE administration, 0.1 mg/kg/h infusion was administered iv. Rats were sacrified by iv potassium chloride. The lungs were then removed, fixed in 10% buffered formalin for 3 days and embedded in paraffin. They were graded on a scale of 0-3 according to the aggregation of neutrophils. Results: There was intense neutrophil migration in Group E (grade 2, 3). However, although mild neutrophil migration was obtained in 70% of the rat lungs in Group ME (grade 1, 2), it was recorded in only 30% of Group PE (grade 1). Conclusion: The sepsis model induced by ECE and compared with midazolam, propofol anaesthesia is associated with less neutrophil infiltration. In the light of the literature, propofol attenuate the free-radical-mediated lipid peroxidation and systemic inflammation in patients.
Keywords: Sepsis; lung; neutrophil; propofol; midazolam; rat; RESPIRATORY-DISTRESS-SYNDROME; IN-VITRO; ANESTHETIC AGENTS; INTERLEUKIN-8; PHAGOCYTOSIS; NEUTROPHILS; THIOPENTONE; SURGERY; INJURY; SEPSIS